2013
DOI: 10.1371/journal.pone.0061971
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing Effects and Mechanisms of Afzelin against UVB-Induced Cell Damage

Abstract: Ultraviolet (UV) radiation induces DNA damage, oxidative stress, and inflammatory processes in human keratinocytes, resulting in skin inflammation, photoaging, and photocarcinogenesis. Adequate protection of skin against the harmful effects of UV irradiation is essential. Therefore, in this study, we investigated the protective effects of afzelin, one of the flavonoids, against UV irradiation in human keratinocytes and epidermal equivalent models. Spectrophotometric measurements revealed that the afzelin extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 59 publications
3
45
0
Order By: Relevance
“…Both the TBARS and SOD levels may be used as markers of oxidative stress. Most products and vitamin-based treatments used to prevent skin aging involve antioxidation properties [27][28][29]. In this study, the data suggest that overexposure to UVB irradiation leads to increased TBARS level and decreased SOD level, resulting in significant skin damage.…”
Section: Discussionmentioning
confidence: 70%
“…Both the TBARS and SOD levels may be used as markers of oxidative stress. Most products and vitamin-based treatments used to prevent skin aging involve antioxidation properties [27][28][29]. In this study, the data suggest that overexposure to UVB irradiation leads to increased TBARS level and decreased SOD level, resulting in significant skin damage.…”
Section: Discussionmentioning
confidence: 70%
“…A number of natural products from plants like phenolics and flavonoids [17], peanut sprout extracts [31], and afzelin [32], etc., have been reported as very useful chemoprevention against oxidative stress. Our present study provides evidence that the plant derivative AKBA is a promising regimen for chemoprevention through activation of the Nrf2-ARE-driven antioxidant pathway; researchers showed that AKBA suppresses tumorigenesis, inflammation, and neuroprotection [8,33].…”
Section: Discussionmentioning
confidence: 99%
“…Afzelin has been reported to exhibit antioxidant, DNA-protective, ultra-violet radiation-absorbing and antiinflammatory properties (36). In addition, a recent study revealed that afzelin inhibits breast cancer cell proliferation by stimulating apoptosis (5).…”
Section: Discussionmentioning
confidence: 99%